BUSINESS ANALYSIS ENLARGMENT TILAPIA (Oreochromis niloticus) AT FLOATING NET CAGES IN THE VILLAGE TANJUNG SANI SUB-DISTRICT AGAM WEST SUMATRA PROVINCE - Jhoni Afrin; Hendrik '; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
These research about business analysis enlargement Tilapia (Oreochromis niloticus) at floating net cages, was held in march 2015 in the village Tanjung Sani. The purpose of the research to know how large cost of investment and profits obtained from the business enlargement Tilapia at floating net cages 10 bags and 20 bags, this research also aims to find out how the feasibility of busisness if revisited from investment criteria.This research shows that floating net cages business 10 bags needed Rp 305.820.000 investment, and for 20 bags needed Rp 594.920.000 invesment. The income obtained from one production periode to floating net cages for 10 bags business is Rp 342.000.000 and Rp 648.000.000 for 20 bags floating net cages business. The criteria investment of floating net cages business for 10 bags was valued by NPV Rp 622.009.880 BCR 1,25 and IRR 76,07 % and for floating net cages business for 20 bags was valued by NPV Rp 1.326.392.250 BCR 1,27 and IRR 76,20 %.Key Words: Floating Net Cages, Investment, Income, and Financial Analysis